Adenosine monophosphate-activated protein kinase modulation by berberine attenuates mitochondrial deficits and redox imbalance in experimental diabetic neuropathy. (15th March 2018) - Yerra, Veera Ganesh; Kalvala, Anil Kumar; Sherkhane, Bhoomika; Areti, Aparna; Kumar, Ashutosh
Abstract: Adenosine monophosphate-activated protein kinase (AMPK) has been studied for its myriad metabolic and mitochondrial benefits in several chronic diseases. Recent studies have uncovered its therapeutic potential against mitochondrial dysfunction in cultured dorsal root ganglion (DRG) neurons isolated from streptozotocin (STZ) induced diabetic rats. The present study is aimed at evaluating the pharmacological efficacy of berberine (BRB), a natural AMPK activator against experimental diabetic neuropathy (DN) phenotype developed in STZ (55 mg/kg, i.p. ) induced diabetic rats and neurotoxicity in high-glucose (30 mM) stimulated neuro 2a (N2A) cells. Diabetic-rats have shown reduced expression of p-AMPK (Thr 172) in sciatic nerves with a consequent reduction in mitochondrial biogenesis and autophagy. BRB (50 & 100 mg/kg, po) administration to diabetic rats for 2-weeks rescued mitochondrial functional deficits and autophagy impairment by increasing the p-AMPK expression. BRB administration also augmented the NEF-2 related factor 2 (Nrf2) mediated endogenous antioxidant defence systems to restrain neuronal damage and neuroinflammation. These effects after BRB administration resulted in enhanced conduction velocity, improved nerve blood flow and attenuated hyperalgesia. Similarly, BRB exposure (5 & 10 μM) to N2A cells attenuated high glucose induced ROS generation, mitochondrial membrane depolarization through the promotion of Nrf2 mediated antioxidant defence systems. BRB exposure augmented peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) mediated mitochondrial biogenesis in neuronal cells. Results from this study signify the importance of mitoprotection conferred by BRB in DN and can be used as a preliminary basis for further molecular exploration. Graphical abstract: Graphical abstract showing the therapeutic effects of Berberine (BRB) in experimental DN. BRB inhibits mitochondrial complex I partially and thereby cause increased AMP/ATP ratio, which stimulates AMPK activity (Thr 172 phosphorylation). Phosphorylated AMPK produces several beneficial therapeutic effects in DN either by transcriptional regulation or by direct phosphorylation of several cellular targets. Its activation can also exert changes in NAD pool to stimulate SIRT1 activity. SIRT1 activation is also observed to produce similar metabolic and mitochondrial effects as that of AMPK.(AMPK: AMP activated protein kinase, mTOR: mammalian target of rapamycin, Nrf2: Nuclear factor (erythroid-derived 2)-like 2, NF-κB: Nuclear factor kappa B, PGC-1α: Peroxisome proliferator-activated receptor gamma coactivator 1-alpha). Highlights: AMPK inactivation might underlie mitochondrial dysfunction in experimental DN. Berberine promotes mitochondriogenesis and autophagy in DN by AMPK induction. Berberine mitigates oxidative damage and neuroinflammation in experimental DN.